2018
DOI: 10.1088/1361-6471/aace6f
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis of the Higgs boson decay Hgg up to ${\alpha }_{s}^{6}$-order level using the principle of maximum conformality

Abstract: Using the newly available α 6 s -order QCD correction to the Higgs decay channel H → gg, we make a detailed discussion on the perturbative properties of the decay width Γ(H → gg) by using the principle of maximum conformality (PMC). The PMC provides a way to eliminate the conventional renormalization scheme-and-scale ambiguities, which uses the renormalization group equation to determine the optimal running behavior of the strong coupling constant at each order via a recursive way. Even though there is no ambi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…where the error is the residual scale dependence, which mainly comes from the NLO-terms. As a comparison, it has been found that the renormalization scale uncertainty for N 4 LO using the conventional scale setting is +2.1 −1.3 KeV [145], which is larger than that of PMC prediction but is also small. This indicates that if one knows enough higher-order terms, the conventional scale uncertainty can also be suppressed to a certain degree.…”
Section: The Residual Renormalization Scale Dependencementioning
confidence: 95%
See 1 more Smart Citation
“…where the error is the residual scale dependence, which mainly comes from the NLO-terms. As a comparison, it has been found that the renormalization scale uncertainty for N 4 LO using the conventional scale setting is +2.1 −1.3 KeV [145], which is larger than that of PMC prediction but is also small. This indicates that if one knows enough higher-order terms, the conventional scale uncertainty can also be suppressed to a certain degree.…”
Section: The Residual Renormalization Scale Dependencementioning
confidence: 95%
“…In some cases, a weak perturbative convergence may be exist in a PMC scale; the residual scale dependence for this particular scale may be large, leading to a comparatively larger residual scale dependence for the pQCD approximant. As an example, it has been found that there is comparatively large µ r dependence for the NLO PMC scale Q 2 for H → gg process, leading to a larger residual scale dependence for H → gg decay width [128,145]. Figure 7 shows that the precision of Q 2 increases as more loop terms have been taken into consideration.…”
Section: The Residual Renormalization Scale Dependencementioning
confidence: 99%
“…This dependence is expected to be suppressed when one includes higher loop terms. An example can be found for Higgs-boson decay H → gg[38].…”
mentioning
confidence: 99%
“…the logarithm L = ln Before applying the PMC to the R-ratio, we first transform the MS-scheme pQCD series (3) into the one under the minimal momentum space subtraction scheme (mMOM) [29,30]. This transformation avoids the confusion of distributing the n f -terms involving the three-gluon or fourgluon vertexes into the β-terms [31][32][33][34]. This transformation can be achieved by using the relation of the running coupling under the mMOM-scheme and the MS-scheme, e.g.…”
Section: Calculation Technologymentioning
confidence: 99%